2022
DOI: 10.2991/ahsr.k.220106.029
|View full text |Cite
|
Sign up to set email alerts
|

Biomotor Analysis of Speed and Flexibility in the Karate Talented Athletes Coaching in the Special Region of Yogyakarta

Abstract: Biomotor speed and flexibility are important components that must be possessed by a karate athlete. This study aims to analyze the biomotor abilities of speed and flexibility in karate talented athletes in the Special Region of Yogyakarta. The research sample consisted of 20 karate athletes who participated in the talented athlete coaching program in the Special Region of Yogyakarta. The research was conducted in a quantitative descriptive. The data was obtained by using the 50-meter sprint test to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In a recent study, it was found that karate athletes had high levels of flexibility, with 80% of athletes reaching the "perfect" index in the sit and reach test (Srianto & Siswantoyo, (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was found that karate athletes had high levels of flexibility, with 80% of athletes reaching the "perfect" index in the sit and reach test (Srianto & Siswantoyo, (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility in fighting sports is a fundamental physical capacity due to the necessary joint amplitude, both in attack techniques and in defence techniques (Chaabene et al, 2012;Soares et al, 2005). In a competition, factors such as speed and flexibility play an important role in the execution of effective movements (Srianto & Siswantoyo, (2022).…”
Section: Discussionmentioning
confidence: 99%